Lipid thermotropic transitions in Triatoma infestans lipophorin - Soulages, Jose Luis (1989)
The structure and lipid thermotropic transitions of highly purified lipophorin of Triatoma infestam were examined by several techniques: steady-state fluorescence polarization of 1,6-diphenyl-1,3,5-hexatrien(eD PH), cis-parinaric acid (cis-PnA) and tram-parinaric acid (tram-PnA), light scattering fluorescence energy transfer between the lipophorin tryptophan residues and the bound chromophores, DPH, tram-parinaric acid cis-parinaric acid, gel electrophoresis, and gel filtration. Fluorescence polarization of PnAs and DPH revealed a reversible lipid thermotropic transition in intact lipophorin at about 2OoC and 18OC, respectively. In lipophorin, lipid dispersion fluorescence polarization of DPH detected a lipid transition approximately at 2OoC, while tram-PnA showed a gel phase formation at a temperature below 3OOC. Similar experiments in which tram-PnA was incorporated into diacylglycerols and phospholipids extracted from the lipophorin revealed gel phase formation below 3OoC and 24OC, respectively. Light scattering measurements showed that lipophorin particles aggregate irreversibly at 45OC, increasing the molecular weight, as determined by gel filtration on Sephacryl S-300, from 740,000 to values larger than 1,500,000. The particle aggregation did not change the physical properties of the lipophorin studied by fluorescence polarization, indicating that the aggregation is apparently a non-denaturing process. Energy transfer between the lipophorin tryptophans and the bound chromophores cis-PnA, tram-PnA, and DPA revealed a different locationo f the fluorescent probes within thleip ophorin. Temperature-dependence on the energy transfer efficiency for all probes confirmed a change in the ordering of the lipophorin lipids at 24'C-